2016
DOI: 10.1111/ajsp.12139
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations between maternal and paternal parenting and physical and relational aggression

Abstract: A large number of studies have demonstrated that negative parenting is associated with greater levels of aggression (relational and physical) among school-age children in Western cultures. However, the investigation of this association for children in non-Western cultures is still in its infancy. The present study examines the associations between maternal and paternal parenting behaviours (conflict with the child, physical aggression toward the child and relational aggression toward the child) and forms of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Fathers, as role models, may exert a stronger impact on boys, who may witness and experience their fathers' behaviors more directly. The association between negative paternal parenting behaviors and boys' physical attacks (Kawabata & Crick, 2016), as suggested by previous research, further supports the gender-specific influence of paternal co-parenting bias. Researchers exploring the association between paternal coparenting and adolescent cyberbullying perpetration should consider the gender of adolescents, recognizing the differential impact on boys and girls.…”
Section: The Moderating Role Of Gendersupporting
confidence: 82%
“…Fathers, as role models, may exert a stronger impact on boys, who may witness and experience their fathers' behaviors more directly. The association between negative paternal parenting behaviors and boys' physical attacks (Kawabata & Crick, 2016), as suggested by previous research, further supports the gender-specific influence of paternal co-parenting bias. Researchers exploring the association between paternal coparenting and adolescent cyberbullying perpetration should consider the gender of adolescents, recognizing the differential impact on boys and girls.…”
Section: The Moderating Role Of Gendersupporting
confidence: 82%
“…Finally, although the association between negative parenting and children's physical aggression has been well-documented, the influence of adverse parenting on the development of relational aggression has been less studied (Kawabata and Crick, 2016). Some researchers have analyzed the association between physical punishment and a global measurement including both physical and relational aggression (Söderberg et al, 2016), and several studies have found that parenting characterized by psychological control increases children's relational aggression (Kawabata et al, 2011;Kuppens et al, 2013).…”
Section: Parental Use Of Corporal Punishment and Child Aggressionmentioning
confidence: 99%